Pengaruh Instagram sebagai Social Media Marketing terhadap Perilaku Konsumtif Wanita di Kota Sampit - Ananda, Dea (Universitas Darwan Ali, 2022)
This study aims to determine the effect of Instagram as a social media marketing on consumptive behavior. The population of this study was women in the city of Sampit with an age range of 17-26 years with a sample of 100 respondents. The sampling method used purposive sampling with an instrument in the form of a Likert scale questionnaire. The data analysis method used is multiple linear regression. The results show that Instagram as social media marketing has a positive and significant effect on consumptive behavior. This means that women in the city of Sampit have consumptive behavior. Therefore, if the information on products specific to women's fashion is further improved, information on the latest goods is continuously developed, and advertising appearances on Instagram are made more attractive, then the consumptive behavior of women viewing Instagram will increase.